PTU-016a Functional defects in circulating monocytes may contribute to susceptibility to infection in alcoholic hepatitis. (28th May 2012) - Vergis, N; Antoniades, C G; Zingarelli, V; Abeles, R D; Ma, Y; Shawcross, D; Janmohamed, A; Patch, D; Rosenberg, W; Kennedy, P; Foster, G; Khan, S; et al.
Abstract : Introduction: Infection is common in patients with severe alcoholic hepatitis (AH) and a significant contributor to mortality. Monocytes play an important role in bacterial elimination by phagocytosis, using intracellular oxidative killing and antigen presentation. Our study sought to evaluate monocyte phagocytosis and scavenger receptor expression in AH. Methods: Monocytes were collected from 14 patients with AH (DF >31, prior to treatment) and 22 healthy controls (HC). Using FACS, monoclonal antibodies to scavenger receptors (CD36, -64, -163, -206, DCIR) and HLA-DR were used for immunophenotyping. Subsequently, ex-vivo monocyte phagocytosis and oxidative burst activity was assessed using FITC-labelled opsonised and non-opsonised Escherichia coli . Results: The expression of scavenger receptors was deranged. In CD14+CD16- (classical) monocytes, CD163 MFI was reduced in AH compared to controls (587 vs 403; p=0.05). CD36, -206 and DCIR expression was similar between HC and AH patients but CD64 MFI was raised (6002 vs 12599; p<0.001). The proportion of monocytes phagocytosing E coli was lower in AH compared to HC (77% vs 87%; p<0.03) but this was not a result of complement deficiency as phagocytosis did not depend on whether the bacteria were opsonised or not (73% vs 80%; p=0.9). The proportion of monocytes capable of generating an oxidative killing burst in response to phagocytosed E coli was markedly reduced (84% vs 47%; p<0.004) in AH patients compared to HC [Abstract PTU-016a figure 1 ]. Antigen presentation was also impaired: classical monocytes had significantly lower HLA-DR expression in AH compared to controls (73% vs 35%; p=0.002), with similar levels of HLA-DR expression detected in the CD14+CD16+ monocyte subset (94% vs 74%; p=0.4). Conclusion: It appears that there are a number of functional defects in circulating monocytes in patients with AH. The marked impairment of phagocytosis and intracellular killing may contribute to the increased susceptibility to infection in this group of patients. Competing interests: None declared.